Reinventing the male homosexual : the rhetoric and power of the gay gene - Brookey, Robert Alan, 1959- (Race, gender, and science., 2002)
Reinventing the Male Homosexual: The Rhetoric and Power of the Gay Gene examines the assumption that embracing the biological research on homosexuality is a viable political strategy for the gay rights movement. The biological argument for gay rights is treated as a "bio-rhetoric," a means of incorporating scientific research into public debates. The book investigates the biological research on which this gay rights argument is based, and explores how male homosexuality is conceptualized in the fields of